# algebra

posted by .

What is an equivalent form of the following equation 2x-3y=3

• algebra -

2x-3y-3=0
x = 3(y+1)/2

y = 2/3 x - 1

y = 2/3 (x-3/2)

## Similar Questions

1. ### algebra

Rewrite the following as an equivalent logarithmic equation.Do not solve. y^t = x answer logy+logt=logx-is this right also Express as an equivalent expression that is a sum of logt (3ab) the t is at the bottom of the g answer log3+loga+logb …
2. ### Inter algebra

Simplify the following expression, and rewrite it in an equivalent form with positive exponents. (10x-5)-5
3. ### Algebra 2

If you were to use the substitution method to solve the following system, choose the new equation after the expression equivalent to x from the first equation is substituted into the second equation. x – 2y = 2 x + 3y = 17
4. ### algebra

Can someone please help me? Thanks! simplify the following expression, and rewrite it in an equivalent form with positive exponents(4x^2)-^2
5. ### algebra

Simplify the following expression, and rewrite it in an equivalent form with positive exponents. 10x^3y^3 -------- 40x^-3y^-4
6. ### algebra

simplify the following expression, and rewrite it on equivalent form with positive exponets. -16x7y4z ---------- 20x2z3
7. ### algebra 2

If you were to use the substitution method to solve the following system, choose the new equation after the expression equivalent to x from the first equation is substituted into the second equation. x + y = 2 3x + 2y = 9
8. ### algebra

Which equivalent form following equation 2x-3y=3 need help doing test thank you
9. ### algebra

Which equivalent form following equation 2x-3y=3